Internet governance and development agenda - Kasinathan, Gurumurthy; Gurmurthy, Anita (2008)
The internet is a building block of the information society and as such its governance is an important issue. What are the issues related to internet governance and how can they be dealt with? How may the Internet Governance Forum contribute to participatory decision-making? These are important issues ahead of the next IGF meeting, to be held in India in end-2008. - Reproduced.
Keywords: Internet